Benthic foraminifera counts and benthic foraminifera accumulation rates from IODP Hole 371-U1506A - Gastaldello, Maria Elena; Agnini, Claudia; Alegret, Laia (PANGAEA, 2023)
Benthic foraminifera counts from IODP Site U1506. We recognized a total of 98 taxa (84 calcareous and 14 agglutinated) at the species or higher taxonomic level. The species with relative abundance >2% in at leastone sample, were systematically described to provide an updated taxonomic study in the Tasman Sea during the Late Miocene - Early Pliocene. On the same dataset we calculated the benthic foraminiferal accumulation rates to provide new insights into the paleoenvironmental and paleoceanographic changes across the Late Miocene - Early Pliocene Biogenic Bloom. We differentiated three intervals with paleoenvironmental significance across the study record, and we redefined the position of Interval 2 (6.7 to 4.9 Ma) previously defined in Gastaldello et al. (2023) and defined the new Interval 3 (4.9 to 4.5 Ma).
Keywords: Benthic foraminifera; Benthic foraminifera assemblages